1995
DOI: 10.1007/bf01691382
|View full text |Cite
|
Sign up to set email alerts
|

Infection rate ofIxodes ricinus ticks withBorrelia afzelii, Borrelia garinii, andBorrelia burgdorferi sensu stricto in Slovenia

Abstract: In spring 1993, Ixodes ricinus ticks were collected from six regions of Slovenia to determine their overall rate of infection with Borrelia burgdorferi sensu lato and to assess the frequency of individual species in these tick populations. Ticks were dissected and midgut tissue inoculated into modified Barbour-Stoenner-Kelly (BSK II) medium. Borrelia isolates were differentiated into separate species using species-specific polymerase chain reaction (PCR) primers and by large restriction fragment pattern (LRFP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
19
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 27 publications
4
19
0
Order By: Relevance
“…On a subtropical island in the Atlantic, northwest of continental Africa, the infection rate of I. ricinus by B. burgdorferi was 1.3% (Matuschka et al 1994). The 30.5% infection rate we observed in Tunisia is within the range reported from European countriesÑ13.8% in Spain (Mareuez and Constan 1990), 9.6% in Belgium (Martin et al 1990), 5Ð50% in Switzerland , Gern et al 1992, 20% in the Netherlands (Rijpkema et al 1994), 18% in Germany (Matuschka et al 1992), 13% in Slovenia (Strle et al 1995), 45% in Croatia (Rijpkema et al 1996), and 12.4% in France (Zhioua et al 1996). Additional studies are needed to determine the infection rates of immatures and to identify the reservoir hosts of B. burgdorferi sensu lato in Tunisia.…”
Section: Resultssupporting
confidence: 82%
“…On a subtropical island in the Atlantic, northwest of continental Africa, the infection rate of I. ricinus by B. burgdorferi was 1.3% (Matuschka et al 1994). The 30.5% infection rate we observed in Tunisia is within the range reported from European countriesÑ13.8% in Spain (Mareuez and Constan 1990), 9.6% in Belgium (Martin et al 1990), 5Ð50% in Switzerland , Gern et al 1992, 20% in the Netherlands (Rijpkema et al 1994), 18% in Germany (Matuschka et al 1992), 13% in Slovenia (Strle et al 1995), 45% in Croatia (Rijpkema et al 1996), and 12.4% in France (Zhioua et al 1996). Additional studies are needed to determine the infection rates of immatures and to identify the reservoir hosts of B. burgdorferi sensu lato in Tunisia.…”
Section: Resultssupporting
confidence: 82%
“…Indeed, adult I. ricinus, which have ingested a greater number of potentially infected meals than nymphs, usually show a higher prevalence of B. burgdorferi s.l. infection than immature stages (Aeschlimann et al 1986, Strle et al 1995, Younsi et al 2001. Borrelia Infection in Lizards.…”
Section: Resultsmentioning
confidence: 99%
“…Dilution series of Borrelia DNA showed that 1,000 Borrelia genome equivalents corresponded to a ct value of 30, 100 genome equivalents corresponded to 34, 10 genome equivalents corresponded to 38, and 1 genome equivalent corresponded to more than 40 cycles. (26). Interestingly, three of the 1,055 ticks examined were positive for B. burgdorferi sensu lato but the isolates could not be classified into one of the three species, as their T m (58.6°C) differed from those of the others: B. burgdorferi sensu stricto (63°C), B. garinii (68°C), and B. afzelii (72.5°C).…”
Section: Discussionmentioning
confidence: 96%